Water solubility is essential for fluorescent probes to image hypochlorous acid in live cells. Issue 71 (27th July 2018) - Xing, Panfei; Zhang, Zhe; Niu, Yiming; Qi, Yaning; Dong, Lei; Wang, Chunming
Abstract : Our findings, for the first time, highlight the importance of water-solubility of fluorescent probes for HClO imaging. Abstract : We synthesised four probes and compared their HClO-detecting ability in different solvents. The data showed that only hydrophilic probes could sensitively and accurately detect HClO in live cells. Meanwhile, the addition of organic solvents, as is commonly practised, weakens the oxidising capacity of HClO and thus generates inaccurate outcomes.